1992
DOI: 10.1007/bf02284965
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oral contraceptive agents on kidney function and protein metabolism

Abstract: The present study was an investigation of the effect of oral contraceptives on kidney function as well as a brief examination of protein metabolism, since glomerular filtration rate depends to a large extent on daily protein intake. 28 healthy women not taking contraceptives and 46 healthy women (aged 20-28 y) on one of three different types of oral contraceptive (combination preparations) were investigated [Minulet/Femovan, Marvelon, Diane]. In all groups on oral contraceptives the endogenous creatinine clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The combined oral contraceptive pill has previously been associated with an increased gut transit time , decreased absorption of a variety of vitamins and minerals , and decreased serum albumin levels . It has been found, as well, to increase both endogenous creatinine clearance and the nitrogen excretion rate/daily protein intake ratio and to inhibit myofibrillar protein synthesis .…”
Section: Discussionmentioning
confidence: 99%
“…The combined oral contraceptive pill has previously been associated with an increased gut transit time , decreased absorption of a variety of vitamins and minerals , and decreased serum albumin levels . It has been found, as well, to increase both endogenous creatinine clearance and the nitrogen excretion rate/daily protein intake ratio and to inhibit myofibrillar protein synthesis .…”
Section: Discussionmentioning
confidence: 99%
“…19 The administration of OC has also been found to increase creatinine clearance in young women studied while receiving a free sodium intake. 57 Kang et al reported significant increases in systolic BP, renal vascular resistance, and filtration fraction in OC users compared with nonusers and showed that these differences were at least partially abolished by angiotensin II blockade. 58 Based on their data, the authors have suggested that despite humoral evidence of renin angiotensin system activation by OC, the tissue response may actually be down-regulated, perhaps at a receptor level.…”
Section: Female Sex Hormones and The Renal Hemodynamic Response To Saltmentioning
confidence: 99%
“…There are few data on the renal hemodynamic effects of OC. 19,[55][56][57] An early study by Hollenberg et al has shown that OC in healthy young women reduces the effective renal plasma flow, an effect that appears to be due to an activation of the renin-angiotensin system by OC. 19 The administration of OC has also been found to increase creatinine clearance in young women studied while receiving a free sodium intake.…”
Section: Female Sex Hormones and The Renal Hemodynamic Response To Saltmentioning
confidence: 99%
“…The RAS is activated by oral contraceptives, probably via an estrogen response element present in the promoter region of angiotensinogen (74). Oral contraceptives may also increase creatinine clearance (14). Men have higher plasma renin activity than agematched women (72), as well as higher blood pressures (121,161).…”
Section: Sex Steroids and Diabetic Kidney Diseasementioning
confidence: 99%